Pengaruh Budaya Kerja dan Jam Kerja pada Perusahaan PT Kwangduk Worldwide - Ageng Kanda Saepudin S; Tika Nurrahmah (JURNAL RISET MANAJEMEN (JURMA), 2024)
Researchers aim to analyze the influence of work culture and working hours on employee performance at PT Kwangduk Worldwide. PT. Kwangduk Worldwide is a men's apparel company that has been around for 40 years with 100% export sales and an address at Jl Raya Cipeundeuy, Ds. Cikalong, Kec. Cikalong Wetan, West Bandung, West Java, 40556, Indonesia. This research aims to determine and analyze work culture, working hours, performance, and the influence of work culture and working hours on the performance of production department employees at PT. Kwangduk Worldwide. By examining the influence of work culture and working hours, we know that work culture and working hours have a very positive influence on the running of a company. The research method used is a descriptive and quantitative method, data was obtained directly through questionnaires to 10 respondents who were production employees at PT. Kwangduk Worldwide. Employee performance is influenced simultaneously by work culture and working hours, meaning that the ability of performance variables can be explained by variations in work culture variables (X1) and variations in working hours variables (X2). Where researchers also give questions and statements to respondents to fill in so they can collect data according to the aspects studied. Based on the research results, it shows that simultaneously work culture and working hours have a significant effect on employee performance and partially work culture and working hours have a significant effect on the performance of employees in the production department of PT. Kwangduk Worldwide.